Inland Waters Dynamics and Ecology - Devlin, Adam; Pan, Jiayi; Manjur Shah, Mohammad (IntechOpen, 2021)
Inland waters, lakes, rivers, and their connected wetlands are the most important and the most vulnerable sources of freshwater on the planet. The ecology of these systems includes biology as well as human populations and civilization. Inland waters and wetlands are highly susceptible to chemical and biological pollutants from natural or human sources, changes in watershed dynamics due to the establishment of dams and reservoirs, and land use changes from agriculture and industry. This book provides a comprehensive review of issues involving inland waters and discusses many worldwide inland water systems. The main topics of this text are water quality investigation, analyses of the ecology of inland water systems, remote sensing observation and numerical modeling methods, and biodiversity investigations.